Acceptance and compliance with micronutrient powder (MNP) among children aged 6–23 months in northern Nigeria - Stephen R. Kodish; Chris Isokpunwu; Tobi Osunkentan; Annette Imohe; Clara Ladi Ejembi; Stanley Chitekwe; Arjan de Wagt; Pragya Mathema (PLOS Global Public Health, 2022)
This study sought to understand the utilization patterns and influencing factors of micronutrient powder (MNP) use among children aged 6–23 months in northern Nigeria as part of formative research to inform the design of an infant and young child feeding (IYCF) intervention. It had an iterative, multi-phase design whereby mixed methods data were collected from 144 households participating in an 8-week home-feeding trial. During the first four weeks, 12-hour direct observations were conducted with 24 households using MNP. Over the next four weeks, 18 of the same households were observed. In-depth interviews were also conducted among 27 caregivers to understand factors related to utilization. Unannounced spot checks (n = 86) were also conducted to gauge MNP compliance. Most households (76.7%) (66/86) adhered to instructions for using MNP (Adamawa (34/44 = 77.3%) and Kebbi (32/42 = 76.2%)). Facilitating factors to MNP adherence were identified, most notably the high ease of utilization, with 90.0% of caregivers indicating the MNP was ‘easy’ or ‘very easy’ to use. Several barriers to MNP compliance were identified and organized into three domains: product-related (e.g. difficulty opening sachet), child-related (e.g. not finishing fortified staple), and caregiver-related (e.g. difficulty making food daily). In Kebbi and Adamawa, MNP was accepted and utilized according to guidelines among most study participants. Findings may be used for scaling up MNP within a more comprehensive IYCF intervention in northern Nigeria.